Plan de manejo ambiental para desechos sólidos hospitalarios generados en el Hospital Básico Machachi del Cantón Mejía Provincia de Pichincha. - Ganchozo Valencia, Eduardo Manuel (2018)
The hospital waste management plan was developed for the Machachi Basic Hospital, located in Mejia canton, to establish a technical waste management method since mismanagement can damage citizenship and the workers; for the management of waste, carried out in the clinic, the program of the Ministry of Public Health of Ecuador was used as a reference method, which defines the guidelines that must be taken into account in this pilot plan for hospital waste management and for the identification and description of the environmental impact was created in the Leopold matrix, where interactions and environmental effects were related in the clinic, as well as monitoring, photographic documentation, interviews with workers and visitors of the clinic, all to gather the necessary information for the correct description of the process and the implementation of the environmental management plan. The results obtained in the environmental assessment were the following: 26.31% very significant effects 18.42% significant impact and 28.94% minor impacts. This indicates that the implementation of the pilot plan for hospital waste management is feasible for the hospital. Clinical administration is recommended to implement a pilot plan for hospital waste management to guarantee the safety and well-being of hospital patients and citizens.